Characteristics of severe injuries among children and adolescents in a sub-national trauma registry in Saudi Arabia - Alqahtani, Meshal; Alnasser, Lubna A.; Aldosari, Maram A.; Almuzaini, Yasir; Alqahtani, Abdullah; Albabtain, Ibrahim; Tamim, Hala (Frontiers in Public Health, 2025)
IntroductionChildren and adolescents constitute nearly 30% of the global population, and injuries within this age group represent a significant public health concern worldwide.MethodsA cross-sectional study was conducted across five hospitals within the MNG-HA. The Trauma Registry database extracted all pediatric patients with injuries from 2015 to 2022 who were admitted for at least 1 day to MNG-HA hospitals. The outcome was severe injuries, defined as an Injury Severity Score (ISS) ≥16, and the characteristics of the patients included various demographic, health, and injury-related factors. Bivariate and multivariate logistic regression analyses were reported separately for each age group (0–6, 7–12, and 13–19 years).ResultsOut of 3,382 patients, 16.8% experienced severe injuries, with a higher prevalence among males. Significant associations with severe injuries included drowning, poisoning, and assault in the 0–6 age group; abdominal/spine injuries and motor vehicle crashes, in the 7–12 age group; and poisoning and intentional self-harm in adolescents.ConclusionThis study identifies critical factors associated with severe injuries across age groups, informing targeted interventions to reduce injury risk in Saudi Arabia.